Natural Feed Nitzschia sp. Culture on Laboratory Scale - Susianti, Lena; Affandi, Rangga Idris (Aquaculture Department, University of Mataram, 2024)
Natural feed is fish feed that has the form of microscopic organisms found in waters. Commonly used natural feeds are phytoplankton, zooplankton, protozoa, microcrustaceans, microscopic invertebrates, and others. The need for natural feed is growing in line with the increasing fisheries cultivation efforts. Phytoplankton has a very important role in waters, its ecological function as a primary producer and the beginning of the food chain causes phytoplankton to often be used as a measure of the fertility of waters. One of the phytoplankton that is abundant in waters because of its ability to survive even in extreme conditions and has a fat content is Nitzschia sp., a member of the Bacillariophyceae class. Nitzschia sp. plays an important role as a primary producer and is widely used as natural feed for marine organism larvae such as crustaceans, bivalves, and fish. The purpose of this study was to determine the laboratory-scale Nitzschia sp. natural feed culture technique to support cultivation activities. This research was conducted from March to April 2024 at the Marine Aquaculture Center (BPBL) Lombok, West Sekotong, West Lombok Regency, West Nusa Tenggara. The research methods used are descriptive methods and field observations (surveys). The results that the laboratory scale Nitzschia sp. natural feed culture technique includes equipment sterilization activities, culture preparation, seed distribution, density calculation and harvesting. Factors that affect the growth of Nitzschia sp. are culture media that are free from contamination, initial stocking density, light intensity of 2000-5000 Lux, water quality (pH, salinity, and temperature).